A novel frequency-band-selecting pulsed eddy current testing method for the detection of a certain depth range of defects. (October 2019) - Li, Peng; Xie, Shejuan; Wang, Kedian; Zhao, Ying; Zhang, Lei; Chen, Zhenmao; Uchimoto, Tetsuya; Takagi, Toshiyuki
Abstract: Local wall thinning is one of the major defects in industrial structures and in some cases it generates in a certain depth range of the object structures. In this study, a novel nondestructive testing method called frequency-band-selecting pulsed eddy current testing (FSPECT) is proposed to detect a certain depth range of defects. This novel FSPECT method is based on the frequency-band-selecting strategy as well as the conventional square wave pulsed eddy current testing (PECT) method. In this study, FSPECT method is introduced and the frequency range selection principle of the excitation signal of FSPECT is explained in details at first. Then the simulation of FSPECT for detecting a certain depth range of defects has been performed. In addition, the sensitivities of the proposed FSPECT and the conventional PECT are compared and analyzed. Finally, a comparative experiment of FSPECT method and PECT method is implemented. The superiority of the proposed FSPECT method for detecting a certain depth range of defects is demonstrated through simulation and experiment. Highlights: A novel FSPECT method is introduced and the frequency range selection principle of the excitation signal is explained. The simulation of FSPECT for detecting a certain depth range of defects has been performed. The sensitivities of the FSPECT and PECT methods are compared. It was concluded that FSPECT method has the higher sensitivity. A comparative experiment of FSPECT method and PECT method is implemented. The proposed FSPECT method has more advantages.